The kinetic of mullite crystallization: Effect of water content - de Oliveira, Taysa Cristina; Ribeiro, Clovis Augusto [UNESP]; Brunelli, Deborah Dibbern; Rodrigues, Liana Alvares; Thim, Gilmar Patrocínio (Elsevier, 2010)
The kinetic of mullite crystallization from sol–gel method, with different water content, was investigated under non-isothermal conditions using DTA. The sols were obtained from Al(NO3)3.9H2O (ANN) and Si(OC2H5)4 (TEOS) mixtures by varying the water–alcohol content of the system. The crystalline phase changes were verified by X-ray diffraction (XRD). For a sample prepared using ethanol-based alkoxide solution (M0), only Al-poor mullite (p-mullite) crystallizes at 1000 °C; for the one synthesized with low water concentration (M6) Al-rich mullite (r-mullite) and spinel crystallize together; and for a sample prepared using a water-based alkoxide solution only spinel is formed. Thus, the variation of water contents during the synthesis caused great variations in the course of mullitization process. The average value of the apparent activation energy determined for p-mullite, r-mullite and spinel phase crystallization were found to be E = (899 ± 61) kJ mol−1, E = (1015 ± 272) kJ mol−1 and E = (980 ± 196) kJ mol−1, respectively. These results showed that sample M(0) was a monophasic gel, where aluminum and silicon atoms are mixed at a molecular level while sample M(100) was a diphasic gel, where silicon and aluminum atoms are distributed in a nanometric level. The fast reaction between TEOS and water molecules is responsible for this great difference in the sample's homogeneity. The kinetic model of the crystallization process was determined using Malek's procedure. It was established that the crystallization of p-mullite, r-mullite and spinel phase can be described by Šesták–Berggren autocatalytic model.
Keywords: Mullite; Crystallization; Non Isothermal Kinetic; sol-gel